1990
DOI: 10.1172/jci114709
|View full text |Cite
|
Sign up to set email alerts
|

Growth stimulation by coexpression of transforming growth factor-alpha and epidermal growth factor-receptor in normal and adenomatous human colon epithelium.

Abstract: Autocrine stimulation of the epidermal growth factor receptor (EGF-R), by coexpression of transforming growth factor-a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 31 publications
2
56
0
Order By: Relevance
“…A number of epithelial tumor cells with increased expression of EGFR also produce its ligands, and therefore, leading to enhanced autocrine growth stimulation Van de Vijver et al, 1991;Atlas et al, 1992). EGFR and TGF-alpha are expressed in human colorectal carcinomas (Malden et al, 1989) and in a number of colorectal carcinoma-derived human cell lines (Co ey et al, 1986;Markowitz et al, 1990;Untawalwe et al, 1993). In recent years, approaches involving interference with and/or blocking of EGFRmediated autocrine growth stimulation by anti-EGFR mAbs have been the subject of active investigation in an e ort to control cell proliferation (Mendelsohn 1990).…”
mentioning
confidence: 99%
“…A number of epithelial tumor cells with increased expression of EGFR also produce its ligands, and therefore, leading to enhanced autocrine growth stimulation Van de Vijver et al, 1991;Atlas et al, 1992). EGFR and TGF-alpha are expressed in human colorectal carcinomas (Malden et al, 1989) and in a number of colorectal carcinoma-derived human cell lines (Co ey et al, 1986;Markowitz et al, 1990;Untawalwe et al, 1993). In recent years, approaches involving interference with and/or blocking of EGFRmediated autocrine growth stimulation by anti-EGFR mAbs have been the subject of active investigation in an e ort to control cell proliferation (Mendelsohn 1990).…”
mentioning
confidence: 99%
“…The importance of EGFr activation in the regulation of TGFa, either by EGF or TGFa itself, has been established by the use of EGFr antibodies (Markowitz et al, 1990;Ennis et al, 1989;Imanishi et al, 1989). Although the TGFa promoter has been isolated, little is known about the mechanism of response to EGFr activation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of neutralizing antibodies to both TGFa and the EGFr, and TGFa antisense approaches have all demonstrated that TGFa is an autocrine growthstimulatory factor in colon carcinoma (Markowitz et al, 1990;Burgess, 1991, 1992;Ziober et al, 1993) as well as other tumors Ennis et al, 1989;Imanishi et al, 1989;Malden et al, 1989;Lee et al, 1991). TGFa has also been shown to be an autocrine growth factor in normal cells (Markowitz et al, 1990;Malden et al, 1989;Co ey et al, 1987;Madtes et al, 1988;Bates et al, 1990;Kudlow and Bjorge, 1990;Lewis et al, 1990) and during development (Wilcox and Derynck, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations